2012
DOI: 10.1074/jbc.m112.384271
|View full text |Cite
|
Sign up to set email alerts
|

High Conformational Stability of Secreted Eukaryotic Catalase-peroxidases

Abstract: Background: Eukaryotic secreted KatGs are bifunctional enzymes extensively found in phytopathogenic fungi. Results: Structural peculiarities, mainly in the N-terminal domain, dominate stability and other properties of eukaryotic secreted KatGs. Conclusion:The distinctive requirements of secreted KatGs depend on very specific and fully conserved structural features. Significance: This might be exploited to control plant fungal diseases that are jeopardizing food security worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
0
17
1
Order By: Relevance
“…The crystal structures of KatGs from Haloarcula marismortui (HmKatG; Yamada et al, 2002), Burkholderia pseudomallei (BpKatG; Carpena et al, 2003), Mycobacterium tuberculosis (MtKatG; Bertrand et al, 2004) and Magnaporthe grisea (MagKatG;Zá mocký et al, 2012) have been reported. The X-ray structures revealed that KatGs possess unique covalent bonds formed among the side chains of three distal residues, Met-Tyr-Trp, which are located on the distal side of the haem active site.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of KatGs from Haloarcula marismortui (HmKatG; Yamada et al, 2002), Burkholderia pseudomallei (BpKatG; Carpena et al, 2003), Mycobacterium tuberculosis (MtKatG; Bertrand et al, 2004) and Magnaporthe grisea (MagKatG;Zá mocký et al, 2012) have been reported. The X-ray structures revealed that KatGs possess unique covalent bonds formed among the side chains of three distal residues, Met-Tyr-Trp, which are located on the distal side of the haem active site.…”
Section: Introductionmentioning
confidence: 99%
“…LL1 bears the strictly conserved tyrosine (Y226 by E. coli KatG numbering) which participates in a unique MYW covalent adduct found on the distal side of the heme. 8,18,22,23,[29][30][31][32] Replacement of any of the members of the adduct invariably eliminates catalase activity without appreciably diminishing the peroxidatic capabilities of the enzyme. 30,[32][33][34][35][36][37][38][39] 47 Finally, variants which delete the C-terminal end of LL1 not only eliminate catalase activity as expected, they also produce substantial gains in peroxidatic activity even over other catalase-negative variants (e.g., Y226F), indicating that LL1 may favor catalase over peroxidase activity by also restricting access of electron donors to the heme edge.…”
mentioning
confidence: 99%
“…Recently, the first structures of a eukaryotic bifunctional catalase-peroxidase (KatGs) in the ferric resting 1 and oxoiron 2 state were published. Similar to the prokaryotic counterparts, 3 7 eukaryotic KatGs have two interdependent cooperating redox-active cofactors at their active site, namely a heme b and a unique posttranslationally and autocatalytically formed Met299-Tyr273-Trp140 (MYW) adduct [extracellular Magnaporthe grisea KatG ( Mag KatG2) numbering throughout].…”
mentioning
confidence: 99%
“… 9 , 10 Together with cytochrome c peroxidases, ascorbate peroxidases and hybrid-type peroxidases KatGs comprise Family I of the peroxidase-catalase superfamily. 11 , 12 Besides the MYW adduct mentioned above, further KatG-specific structural peculiarities include (i) a two-domain structure with only the N-terminal domain containing the two redox cofactors and essential catalytic residues, 1 , 3 , 4 (ii) loop insertions that contribute to the architecture of the long and restricted access channel, and (iii) a fully conserved aspartate at the entrance of the substrate channel to the heme cavity. 13 , 14 Mutation of any of these KatG-typical structural features typically reduces the catalase activity without compromising the peroxidase activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation